A Decision Support System for Selecting Employees Eligible for Bonuses at Uflo Technology Indonesia Using the Analytical Hierarchy Process (AHP) Method - Tembusai, Zoelkarnain Rinanda; Santoso, Ahmad Imam; Panjaitan, Dodi Syahputra (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
Decision Support Systems (DSS) play a crucial role in minimizing cognitive biases in human resource management processes, particularly in employee incentive or bonus schemes. This study aims to design, develop, and implement a web-based decision support system to determine which employees are most deserving of annual bonuses at Uflo Technology Indonesia by applying the Analytical Hierarchy Process (AHP) method. Conventional performance evaluations, which are often subjective, have the potential to reduce work motivation and lead to organizational injustice. To address these dynamics, this system objectively evaluates employee performance based on five main criteria: discipline, productivity, teamwork, work quality, and initiative and creativity. Empirical evaluation data is sourced directly from Uflo Technology’s internal systems, including digital attendance records and daily job reports. Through the AHP algorithm, each criterion is analyzed using hierarchical decomposition and pairwise comparison to generate a consistent global priority weight, where the Consistency Ratio (CR) is rigorously tested to ensure it remains ≤ 0.1. The final results of the study show that the system successfully performs automatic evaluation synthesis and alternative ranking. Computational validation using real-world data placed the Dodi alternative at the highest rank with a final score of 0.335. The implementation of this web-based system has proven capable of improving accuracy, transparency, and time efficiency in the managerial decision-making process within a corporate environment.